UNITED STATES OF AMERICA - Dear Major Thulin (Fiep Bulletin - online, 2015)
I wish to congratulate you upon your 80th birthday. You deserve to be honores for your incessant work to create an international organization in physical education which would interchange ideas and materials between the leaders of various nations. The Development of the F.I.E.P. bulletin by you and Mr. O. Kragh should be appreciated the world over.
Keywords: .